A retrospective analysis of discharge summaries from a tertiary care hospital medical oncology unit: To assess compliance with documentation of recommended discharge summary components. Issue 2 (21st June 2021) - Ge, Jingwei; Davis, Alison; Jain, Ankit
Abstract: Background: Discharge summaries are essential for health transition between inpatient hospital teams and outpatient general practices. The patient's outcome is dependent on the quality and timeliness of discharge summaries. Aim: A retrospective analysis was carried out to assess the compliance with recommended documentation of 697 electronic discharge summaries (eDSs) of oncology inpatients discharged in 2018 from the Canberra Hospital according to the National Guidelines of On‐Screen Presentation of Discharge Summaries. Methods and results: Individual medical records were identified and screened for the recommended eDS components according to the National Guidelines. Out of the 17 recommended components, nine components were included in all discharge summaries, two components in more than 99% and two components in 95–96% of discharge summaries. The most frequently omitted components include "information provided to the patient, " "ceased medicine" and "procedures, " and these were omitted in 8, 38 and 82% of discharge summaries, respectively. Conclusion: Overall, most discharge summaries adhered to the national guidelines quite well by including most of the recommended components. However, the discharge summary quality is still inadequate in some domains.